Correction: Corrigendum: ChEC-seq kinetics discriminates transcription factor binding sites by DNA sequence and shape in vivo - Gabriel E. Zentner; Sivakanthan Kasinathan; Beibei Xin; Remo Rohs; Steven Henikoff (Nature Communications, 2017)
Nature Communications6: Article number:8733 (2015); Published: 22 October 2015; Updated 5 June 2017 We have been alerted to an inconsistency regarding the control used as input in the DNA shape analysis shown in Fig. 7 of this paper. As described in the Methods section of the Article, ‘FASTA sequences generated from the previously generated 100 bp windows centered on motif match midpoints were used as input for our DNA shape method for high-throughput prediction of DNA structural features.